Effects of temperature and water pressure on mild steel strength: A comparative study - Md. Abdullah; Md Abdul Muttalib; Zafrin Fatme Alam; Md Mosharrof Hossain; Zahid Ahsan (Results in Surfaces and Interfaces)
This study delves into the dynamic realm of mild steel strength variations under the influence of temperature fluctuations and alterations in water pressure during the rolling process. With a focus on elucidating the nuanced relationship between these factors and steel durability, the research employs a systematic investigation approach. The experimental design involves controlled temperature adjustments and varying water pressure scenarios to assess their impact on the structural integrity and tensile strength of mild steel. Through meticulous analysis and measurement, the study aims to uncover the intricate interplay between temperature, water pressure, and steel strength, providing valuable insights for optimizing rolling processes in industrial settings. The experimental works have been conducted at 870 °C, 890 °C, 910 °C, 930 °C, 950 °C of temperature and 5.800 Kg, 6.000 Kg, 6.200 Kg, 6.400 Kg, 6.600 Kg of water pressure. At 870 °C, 890 °C, 910 °C, 930 °C, 950 °C of temperature, the yield point values are 548 Mpa, 541 Mpa, 533 Mpa, 525 Mpa and 520 Mpa respectively. At 5.800 Kg, 6.000 Kg, 6.200 Kg, 6.400 Kg, 6.600 Kg of water pressure, the yield point values are 521 Mpa, 527 Mpa, 534 Mpa, 538 Mpa, 544 Mpa. The Yield Load, Yield Strength, Maximum Force, Tensile Strength, TS/YS Ratio, and Elongation after Fracture were carried out in the Metrocem and Mohammadi Steel Works Ltd (MSW) laboratory. However, the results of two laboratories are almost similar. The findings aspire to contribute to enhanced manufacturing techniques and the development of more resilient steel products, thereby advancing the understanding of material behavior in mechanical applications.